Analisis Risiko Operasional Pada Pegadaian Syariah KC. Bengkulu di Masa Pandemi Covid-19 - Agustian, Rendi; Iswandi, Deni; Nurhab, Badaruddin (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2021)
Operational risk is an important effort that must be carried out by every company, including sharia pawnshops, as an effort to minimize losses due to risks that occur. This study aims to determine the operational risk management conducted by PT. KC sharia pawnshop. Bengkulu during the covid 19 pandemic. This research method uses a qualitative method with a case study approach. Data collection techniques for this study were collected through interviews with related parties at the research site. The results of this study indicate that operational risk is divided into two, namely risk to customers and risk to sharia pawnshops, including: Submission of information about products that are not comprehensive, limiting office hours, services, increasing operating expenses and decreasing profits. Factors causing operational risk are divided into internal factors from sharia pawnshops and external factors from customers, the way that is done by PT. KC sharia pawnshop. Bengkulu to overcome operational risks that occur is to focus on these two factors, optimizing controlling for all employees (internal) and also optimizing controlling for customers (external).